2012
DOI: 10.1142/s0218495812500069
|View full text |Cite
|
Sign up to set email alerts
|

Switching to Entrepreneurship in Mid Career: A Singaporean Perspective

Abstract: The phenomena of an aging population, changing social and economic circumstances, as well as the existential necessity of mid-life changes form the background to this investigation. Though statistics indicate that there are only a few who have considered entrepreneurship as a desirable and feasible career option in mid life, the option is becoming more attractive as the possibility of lifetime employment with a single employer becomes increasingly remote. The focus of this article is to understand what has mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 53 publications
(84 reference statements)
0
8
0
Order By: Relevance
“…Today, Singapore finds itself with a rapidly aging workforce competing economically in a globalized world (e.g., Harper, 2006). Workforce development policies have therefore shifted to address issues of employability and career adaptability (see Billett, 2011), of which one approach has been to inculcate entrepreneurialism in the workforce (Say & Patrickson, 2012).…”
Section: Sample and Proceduresmentioning
confidence: 99%
“…Today, Singapore finds itself with a rapidly aging workforce competing economically in a globalized world (e.g., Harper, 2006). Workforce development policies have therefore shifted to address issues of employability and career adaptability (see Billett, 2011), of which one approach has been to inculcate entrepreneurialism in the workforce (Say & Patrickson, 2012).…”
Section: Sample and Proceduresmentioning
confidence: 99%
“…SE8 emphasised skills gained through his prior experience (Akola, 2008; Kautonen et al, 2010, 2011, 2014; Say and Patrickson, 2012; Singh and DeNoble, 2003), while drawing on the attributes of his age and how these shaped his SEIs. SE22 described the financial ‘burden’ experienced during the social entrepreneurial process, making him ‘physically sick’, and how ‘resilience’ which came with age helped shape his SEIs:…I didn’t think I had resilience because life has been easy…had a good job, made very good money but I assure people now that I’m resilient.…”
Section: Resultsmentioning
confidence: 99%
“…As such, the dynamic interactions between necessity and fulfilment depict the extent to which participants re-negotiated the role of their age in forming their SEIs, whereby they simultaneously recognised that, although age is often perceived in society as a barrier to economic participation (Balcombe and Sinclair, 2001; Coupland et al, 2008; Razanova, 2010), they do not feel old (Barnhart and Penãloza, 2013; Schafer and Shippee, 2009; Shmerlina, 2015). Rather they perceive age as an opportunity to engage in social entrepreneurial activities (Beehr and Bennett, 2015; Ruhm, 1990; Say and Patrickson, 2012). Our participants disassociated themselves from being ‘necessity social entrepreneurs’ since their positive constructions of age intertwined with their need for fulfilment.…”
Section: Discussion and Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…As past studies have shown, such accumulation of human capital can significantly increase new venture survival, and due attention should be given to this segment of the working population (Rae 2009, Shane 2008, Singh and DeNoble 2003. Moreover, studies have also found that mid-career individuals from this age group are often faced with adversity and challenges when embarking on career transition into entrepreneurship (Say and Patrickson 2012). Future policies or programs can be targeted at this age group to enable them to complete a smoother career transition to become successful entrepreneurs.…”
Section: Concluding Remarks and Implicationsmentioning
confidence: 99%